A decade of the liposome-protein corona: Lessons learned and future breakthroughs in theranostics. (December 2022) - Quagliarini, Erica; Digiacomo, Luca; Renzi, Serena; Pozzi, Daniela; Caracciolo, Giulio
Abstract: A decade has passed since the concept of the protein corona, as originally termed by Dawson and coworkers in 2007, was extended to liposomes. Although the protein binding to liposomes has been known since the 1970 s, deep knowledge of the factors triggering its formation and interaction with living systems in vitro and in vivo was not fully understood. Over the last 10 years, multidisciplinary efforts from chemistry, physics, materials science, biology, toxicology, and immunology were put together to understand the synthetic-biological duality of the liposome-protein corona. Here we focus on the methods employed for characterizing the liposome-protein corona, the categories of factors shaping its composition, and the most relevant applications in the field of nanomedicine, where liposomes are designed for targeted drug delivery, vaccination against cancer and infectious diseases, imaging, and diagnostics. We conclude the review by contemplating future research directions and appealing to researchers, entrepreneurs, and policymakers to recognize the relevance of this field of research. Graphical Abstract: ga1 Highlights: Upon interaction with biological fluids, liposomes are coated by a protein corona. The most relevant applications of the liposome-protein corona include drug delivery, immunomodulation and diagnostics. Recent advances are discussed with examples from a clinical perspective. This review aims to inspire scientists, entrepreneurs, and policymakers in biomedical applications.